The influence of geological structures on the character of the channels of right-bank tributaries of the Dniester river - Бурштинська, Христина; Бубняк, Ігор; Заяць, Ірина; Блажко, Софія; Грицьків, Назар; Burshtynska, Khrystyna; Bubniak, Ihor; Zayats, Iryna; Blazhko, Sofiia; Hrytskiv, Nazar (Видавництво Львівської політехніки, 2024)
У запропонованому дослідженні поставлено завдання визначити вплив геологічних структур на русла найбільших правобережних приток річки Дністер – Стрия, Бистриці та Лімниці. З цією метою здійснено районування річки за морфометричними та гідрологічними характеристиками. Виділено три частини: гірську, передгірську і рівнинну, які кардинально відрізняються характеристиками русел, їхніми змінами в часі та деформаційними процесами. Мета роботи. На підставі дистанційних методів отримання зображень різної розрізнювальної здатності, використання різночасових історичних карт та спеціальних карт дослідити русла правобережних приток Дністра: Стрия, Лімниці й Бистриці від витоків до гирлової частини на впадінні в річку Дністер залежно від геологічних та структурно-літологічних особливостей поверхні. Основні методи дослідження – перетворення різних матеріалів дистанційного зондування, історичних та спеціальних карт з метою дослідження специфічних явищ руслових процесів. Методика передбачає підготовку вхідних матеріалів: історичних топографічних карт; геологічних карт; космічних знімків; прив’язку карт та знімків; опрацювання космічних знімків; векторизацію русел; аналіз русел річок залежно від геологічних структур. Результати. Враховуючи особливості морфології, ширину долини, проявлення і розвиток руслових процесів, річки Стрий, Бистрицю, Лімницю розділено на три ділянки: гірську; передгірську та рівнинну із розвиненими акумулятивними формами. В гірській частині русла всіх трьох річок однорукавні, в передгірській частині простежується багаторукавність, яка зменшується із переходом від ХІХ ст. до ХХІ ст. щодо ширини багаторукавності та кількості рукавів, що свідчить про зменшення модуля стоку. Для рівнинних ділянок русел із нерозвиненими акумулятивними формами простежується чітка тенденція до залежності типу русла від структурно-літологічних особливостей. Оригінальність. Встановлено залежність руслових процесів правобережних приток річки Дністер від геологічних та седиментологічних структур Скибових Карпат та Передкарпатського прогину. Практична значущість. Результати моніторингу руслових процесів необхідно враховувати під час вирішення низки завдань, а саме: будівництва гідротехнічних споруд, проєктування мереж електропередач на перетині з річками, розвитку газопроводів, визначення зон затоплення, наслідків руйнування після повеней, освоювання заплавних земель, встановлення меж водоохоронних зон, управління рекреаційними та прикордонними землями та встановлення міждержавного кордону вздовж річок.

The proposed study aims to determine the influence of geological structures on the features of the channels of the largest right-bank tributaries of the Dniester River – the Stryi, Bystrytsia, and Limnytsia rivers. For this purpose, we conducted zoning of the river based on morphometric and hydrological characteristics. Three parts were identified: mountainous, pre-mountainous area and plain area, which differ significantly in channel properties, their changes over time, and deformation processes. Objective. Based on remote sensing images of various resolutions, the use of historical maps over time, and specialized maps, to investigate the nature of the channels of the right-bank tributaries of the Dniester: Stryi, Limnytsia, and Bystrytsia, from their sources to the estuarine part where they flow into the Dniester River, depending on the geological and lithological features of the surface. The main research methods involve the transformation of various materials from remote sensing, historical, and special maps for the purpose of studying specific phenomena of river processes. The methodology involves the preparation of input materials, including historical topographic maps, geological maps, satellite images, maps and images georeferencing, satellite image processing, river channel vectorization, analysis of river channels depending on geological structures. Results. Considering the morphology, valley width, manifestation, and development of channel processes, the Stryi, Bystrytsia, and Limnytsia rivers were categorized into three sections: mountainous, pre-mountainous and plain area with developed accumulative forms. In the mountainous section, all three rivers have single channels, while in the pre-mountainous section, multichannel patterns are observed, which have decreased from the 19th to the 21st century in terms of the width of multichannelity and the number of channels. This indicates a decrease in the flow modulus. For the plain sections of channels with undeveloped accumulative forms, a clear tendency towards dependence of channel type on structural-lithological features is traced. Originality. The paper has established the dependence of channel processes of right-bank tributaries of the Dniester River on geological and sedimentological structures of the Skole Beskids and Subcarpathian Depression. Practical significance. The results of monitoring channel processes need to be considered in addressing a range of tasks, including the construction of hydraulic structures, designing power transmission networks at river crossings, developing gas pipelines, determining flood zones, assessing the consequences of erosion after floods, land reclamation, establishing water protection zones, managing recreational and border lands, and establishing interstate borders along rivers.
Вплив геологічних структур на характер русел правобережних приток річки Дністер
Keywords: руслові процеси; правобережні притоки; річка Дністер; геологічні та седиментологічні структури; космічні знімки; Скибові Карпати; Передкарпатський прогин; багаторукавність; channel processes; right-bank tributaries; The Dniester River; geological and sedimentological structures; satellite images; Skole Beskids; Precarpathian Depression; multichannelity; 528.9